Participating in the Production of Silk Handicrafts in Phonxay Village, Luangprabang City - vongphachit, sone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aim to study the participation in the production of silk handicrafts in Phon Xai Village, Luangprabang District, as a quantitative research which used questionnaires to collect data from a sample group of 98 people and analyze the data with the statistical program SPSS version 20. The results of the study found that people are most involved in the production and service of silk products, participation in marketing, participation in skills in silk production, and participation in administration and management Production of silk with the average total value is between 0.36-0.42 and the standard deviation is between 0.10-0.65. People are involved in the medium level of participation in the use of information technology and participation in the use of internal potential in production and services, with an average